Carbon Dots for Bacterial Detection and Antibacterial Applications-A Mini review - Anand, Anisha; Manavalan, Gopinathan; Mandal, Ranju P.; Chang, Huan-Tsung; Chiou, Yi-Ru; Huang, Chih-Ching (Current Pharmaceutical Design, 2019)
The prevention and treatment of various infections caused by microbes through antibiotics are becoming less effective due to antimicrobial resistance. Researches are focused on antimicrobial nanomaterials to inhibit bacterial growth and destroy the cells, to replace conventional antibiotics. Recently, carbon dots (C-Dots) become attractive candidates for a wide range of applications, including the detection and treatment of pathogens. In addition to low toxicity, ease of synthesis and functionalization, and high biocompatibility, C-Dots show excellent optical properties such as multi-emission, high brightness, and photostability. C-Dots have shown great potential in various fields, such as biosensing, nanomedicine, photo-catalysis, and bioimaging. This review focuses on the origin and synthesis of various C-Dots with special emphasis on bacterial detection, the antibacterial effect of CDots, and their mechanism.
Keywords: photoactivation